The universal man = Manusia universal - Abdul Razak, Mohd Abbas (Potret Online, 2024)
Philosophically Speaking, the Whole World Belongs to Me and I Belong to the Whole World. All Countries are My Country. For This Reason, I Call Myself the Citizen of the World.